PENGARUH KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA DI SMKN 1 CIHAMPELAS - Titin Kurnia Bungsu; Mulkah Vilardi; Padillah Akbar; Martin Bernard (Departement of Mathematics Education, 2019)
Independence of Learning towards Mathematics Learning Outcomes in SMK 1 Cihampelas. The research method used in this study is a survey method using correlational analysis. Samples were obtained by using simple random sampling techniques totaling 35 students from class X of SMK 1 Cihampelas. Data collection is done using questionnaires and PTS tests. Data analysis was performed using SPSS 23 program assistance consisting of descriptive analysis analysis, test requirements for data analysis and hypothesis testing. Requirements test for data analysis used, namely normality test, and linearity test. Based on the results of the study, conclusions were obtained about the significant positive results between learning independence towards mathematics learning outcomes. The contribution of learning independence to mathematical results is 16% and the remaining 84% is contributed by other variables besides learning independence.